Polymeric ionic liquids (PILs): effect of anion variation on their CO2 sorption - Bhavsar, Rupesh S.; Kumbharkar, Santosh C.; Kharul, Ulhas K. (Journal of Membrane Science, 2012)
A series of polymeric ionic liquids (PILs) based on poly(diallyldimethylammonium chloride), P[DADMA][Cl] as a precursor was investigated by varying anions categorized into carboxylates, sulphonates and inorganic type. For the exchange of chloride from P[DADMA][Cl] by another anion, silver salt of the corresponding anion was preferred. Obtained PILs were investigated for physical properties which are anticipated to affect gas sorption. PILs possessing carboxylate (especially acetate) anion exhibited attractive CO2 sorption capacity as well as sorption selectivity over H-2 and N-2, in Comparison to Other two Categories. PIL with acetate anion, P[DADMA][Ac] possessed appreciable CO2 sorption coupled with high selectivity (S-CO2/S-N2 = 114.3). This crucial finding from this series of PILs was further substantiated by making PIL based on poly(vinylbenzyltrimethylammonium chloride), P[VBTMA][Cl] as a precursor. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Anion exchange; CO2 sorption; Polymeric ionic liquid